Indoor radon measurements in Ny-Ålesund, the northernmost civilian settlement in the world - Pérez-Martínez, Manuel; Jiménez-Gámez, Carlos; López-Gordillo, Francisco Javier; Gordo Puertas, Elisa; Liger-Pérez, Esperanza; Cañete-Hidalgo, Sergio Andrés; Ruiz-Cruces, Rafael; Dueñas-Buey, Mª Concepción (My University, 2015)
Ny-Ålesund is situated at 78° 55´ N, 11° 56´ E on the west coast of Spitsbergen, the largest island in the Svalbard archipelago and is a centre for international Arctic scientific research and environmental monitoring. Since 1916 to 1963 was an old coal mining town. Exposure to indoor radon has been identified as the second leading cause of lung cancer after tobacco smoking. In an indoor environment, there are many factors affecting indoor radon concentrations. Those factors could be different in the Arctic regions. [1] It is well known that the Council Directive 2013/59 / Euratom of 5 December 2013, article 74, says that "Member States shall establish national reference levels for indoor radon concentrations. The reference levels for the annual average activity concentration in air shall not be higher than 300 Bq m -3" so it is important to know the radon concentration in different places. Indoor radon activity measurements were carried out in different locations at Ny-Ålesund: Koldewey base (German base), KingsBay dining room, Marine Laboratory, and Gym facilities with five AlphaE devices from Saphymo GmbH. The AlphaE is an ultra small continuous radon monitor for professional use, based on a silicon diffusion chamber.The calculation of dose is possible due to a user-settable equilibrium factor. Indoor radon measurements were carried out from 3 to 27 September 2014. The values show low average level of indoor radon in the different analyzed buildings, with a geometrical mean of 60 Bq/m3 with a maximun value of 145 Bq/m3 in the Koldewey building. So the radiation exposure levels for workers and scientific personnel represents only a low percentage of the exposure guides for the general population.
Keywords: Radón; Radon-222; Indoor quality air; Artic